RETURN ON INVESTMENT IN THE IMPERSONAL METAL ACCOUNTS OF PALLADIUM - Ivan I. Agafonov (Статистика и экономика, 2016)
A study of investment attractiveness of investing in the precious metals market with respect to impersonal metal accounts of Palladium in the period of sustained growth of its market value over the last year. A methodology for the assessment of the return on those investments, taking into account the profitability of alternative risk-free investment.